2005
DOI: 10.1007/s00261-004-0064-z
|View full text |Cite
|
Sign up to set email alerts
|

Seeding from hepatocellular carcinoma after percutaneous ablation: color Doppler ultrasound findings

Abstract: Clinical and imaging findings of seeding from HCC should be recognized by physicians who perform follow-up ultrasound examinations of patients who are treated with PAT. Early diagnosis of seeding can be reliably made by scanning the abdominal wall with small probes in the area where the previous PAT has been performed. Hypoechoic hypervascular pattern of the seeding nodule allows definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…They concluded that only previous tumor biopsy was associated with extrahepatic tumor seeding. Tarantino et al 22 reported that extrahepatic seeding after PEIT for HCC occurred at a frequency of 0.2% to 1.4%. In the present study, needle biopsies prior to LAT were performed in only two patients (25%).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that only previous tumor biopsy was associated with extrahepatic tumor seeding. Tarantino et al 22 reported that extrahepatic seeding after PEIT for HCC occurred at a frequency of 0.2% to 1.4%. In the present study, needle biopsies prior to LAT were performed in only two patients (25%).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous ethanol injection therapy is a low risk, well-established treatment for small HCCs, but can lead to needle tract implantation (11, 12, 17). Although alcohol was thought to sterilize the needle tract and prevent implantation after PEIT (12), the frequency of needle tract implantation is between 0.2%-1.4% (11, 17).…”
Section: Needle Tract Implantation After Peitmentioning
confidence: 99%
“…Although alcohol was thought to sterilize the needle tract and prevent implantation after PEIT (12), the frequency of needle tract implantation is between 0.2%-1.4% (11, 17). PEIT may increase the risk of needle tract implantation compared with biopsy alone because PEIT requires multiple needle punctures over an extended period, despite the advantage of a smaller caliber needle (21-22 gauge) (11).…”
Section: Needle Tract Implantation After Peitmentioning
confidence: 99%
See 2 more Smart Citations